Smart Metal‐Organic Frameworks (MOFs): Switching Gas Permeation through MOF Membranes by External Stimuli. Issue 2 (18th January 2018) - Knebel, Alexander; Zhou, Chen; Huang, Aisheng; Zhang, Jian; Kustov, Leonid; Caro, Juergen
Abstract: The switching of gas permeation and adsorption on polymers, zeolites, and metal‐organic frameworks (MOFs) by external stimuli like temperature, pressure, light, and electric fields is discussed. Especially MOFs as soft porous crystals are suitable candidates for switching gas transport. If the linker of a MOF contains a cis‐trans switchable azo moiety, switching of the trans state into the cis state reduces gas transport through a MOF membrane. On the other hand, MOFs with dipolar or ionic components can be switched upon polarization with an electric field into polymorphs of the starting MOF. A ZIF‐8 membrane can be switched into a polymorph with a rather stiff lattice, which sharpens the molecular sieving effect of the membrane, and, as an example, the propene/propane selectivity increases. Abstract : Metal‐organic membranes are promising candidates to switch gas transport through a membrane by external stimuli like temperature, pressure, light or electric field. But to determine if switching the gas transport through such a membrane is merely a dream or near reality, intense research and development activities on switching adsorption on metal‐organic frameworks in the near future are expected.